Respiratory syncytial virus hospitalization and mortality: Systematic review and meta‐analysis - Stein, Renato T.; Bont, Louis J.; Zar, Heather; Polack, Fernando P.; Park, Caroline; Claxton, Ami; Borok, Gerald; Butylkova, Yekaterina; Wegzyn, Colleen (Pediatric pulmonology, 2017)
Summary Background: Respiratory syncytial virus (RSV) is a major public health burden worldwide. We aimed to review the current literature on the incidence and mortality of severe RSV in children globally. Methods: Systematic literature review and meta‐analysis of published data from 2000 onwards, reporting on burden of acute respiratory infection (ARI) due to RSV in children. Main outcomes were hospitalization for severe RSV‐ARI and death. Results: Five thousand two hundred and seventy‐four references were identified. Fifty‐five studies were included from 32 countries. The global RSV‐ARI hospitalization estimates, reported per 1,000 children per year (95% Credible Interval (CrI), were 4.37 (2.98, 6.42) among children <5 years, 19.19 (15.04, 24.48) among children <1 year, 20.01 (9.65, 41.31) among children <6 months and 63.85 (37.52, 109.70) among premature children <1 year. The RSV‐ARI global case‐fatality estimates, reported per 1,000 children, (95% Crl) were 6.21 (2.64, 13.73) among children <5 years, 6.60 (1.85, 16.93) for children <1 year, and 1.04 (0.17, 12.06) among preterm children <1 year. Conclusions: A substantial proportion of RSV‐associated morbidity occurs in the first year of life, especially in children born prematurely. These data affirm the importance of RSV disease in the causation of hospitalization and as a significant contributor to pediatric mortality and further demonstrate gestational age as a critical determinant of disease severity. An important limitation of case‐fatality ratios is the absence of individual patient characteristics of non‐surviving patients. Moreover, case‐fatality ratios cannot be translated to population‐based mortality. Pediatr Pulmonol. 2017;52:556–569. © 2016 The Authors. Pediatric Pulmonology. Published by Wiley Periodicals, Inc.